A NEW PILLAR OF JAPANESE FOREIGN POLICY: HE ARC OF FREEDOM AND PROSPERITY— JAPANESE POLICY OWARD THE GUAM ORGANIZATION - ISMAYILZADA, Gursel (CENTRAL ASIA AND THE CAUCASUS, 2008)
On 30 November 2006, Japanese Minister of Foreign Affairs Taro Aso1 delivered a policy speech entitled “The Arc of Freedom and Prosperity: Japan’s Expanding Diplomatic Horizons.”2 The foreign minister later made another speech with this title and clarified the details of his conception on 12 March 2007.In his speech, Taro Aso introduced a new vision of Japanese foreign policy and added a new pillar to it. Until recently, Japanese foreign policy was based on three existing pillars: reinforcement of the Japan-U.S. alliance, international cooperation, most notably under the auspices of the United Nations, and relations with neighboring countries, namely China, Russia and the Republic of Korea.The new pillar of Japanese diplomacy places the emphasis on universal values such as freedom, democracy, the rule of law, fundamental human rights, and the market economy. In his speech, Minister Aso stated that Japan would engage itself to create an Arc of Freedom and Prosperity along the outer rim of the Eurasian continent starting from Northern Europe and the Baltic states, crossing Central and South Eastern Europe, the Caucasus and Central Asia, the Middle East, the Indian continent, and Southeast Asia, and finally reaching Northeast Asia. According to the Minister’s speeches, Japan has been traveling the road to peace and happiness through economic prosperity and democracy and will cooperate with the states of the above-mentioned territories to create a prosperous and stable region. Thus, a region of stability and plenty—the Arc of Freedom and Prosperity—with its basic universal values will begin to take shape. As Minister Aso publicly stated in his speech, Japan will serve as an “escort runner”3 to support the countries of the region that have just entered into this process.